Relations between factor VIIa binding and expression of factor VIIa/tissue factor catalytic activity on cell surfaces. - D. Le; Samuel I. Rapaport; L. Vijaya Mohan Rao (1992)
The kinetics of the binding of rVIIa to cell surface tissue factor (TF) and the resultant expression of VIIa/TF activity were studied. Binding of 125I-rVIIa (10 nM) to cell surface TF required 30-60 min for saturation, whereas VIIa/TF activity was fully expressed toward factor X (F X) on intact monolayers after only 1 min of incubation. At the time only 10-20% of the total VIIa TF complexes present at saturation had formed. Freeze-thawing the monolayers before assay increased VIIa/TF activity up to 30-fold, and the time course of its expression was similar to that of TF-specific binding of VIIa to the monolayers. Equilibrium binding revealed a single high affinity binding class of TF sites on intact monolayers for rVIIa with a Kd of 1.6 nM. Experiments with active-site inhibited rVIIa yielded evidence for two populations of VIIa. TF complexes on intact monolayers: (1) a minor population (less than 20%) that formed within 1 min of incubation and accounted for all VIIa/TF activity toward F X present on the intact monolayers, and (2) a major population that was inactive toward F X on intact monolayers but which was fully active after the monolayers were lysed. Tissue factor pathway inhibitor (TFPI).F Xa complexes inhibited the VIIa/TF activity of the first population, i.e. of the complexes active on intact monolayers, half maximally at a concentration of 0.2 nM TFPI. TFPI/Xa also bound to the second population of VIIa.TF complexes on intact monolayers and inhibited their expression of VIIa/TF activity following cell lysis with a half-maximal inhibitory concentration of 2.0 nM. The potential physiologic implications of these findings are discussed.